At Home, At War : Domesticity and World War I in American Literature - Haytock, Jennifer Anne (Book collections on Project MUSE., 2003)
This study demonstrates that such literary divisions as war novel and domestic novel limit readers' understanding of the ways these categories rely on and respond to each other. Haytock argues that gender creates an ideological context through which both domesticity and war are viewed and understood; issues of home and violence are intricately related for U.S. authors who wrote about the First World War. Haytock explores what war and domestic texts represent in light of the deconstructionist said in its cultural and historical context and seeing what is not said. Readers take food, shelter, and clothing for granted, and yet the way we treat them is part of what allows us to define ourselves as civilized. In war novels and domestic novels by Temple Beiley, Ellen, Glasgow, Edith Wharton, Willa Cather, John Dos Passons, Thomas Boyd, Ernest Hemingway, William Faulkner, and Eudora Welty, the idea of home and domestic rituals contribute to the creation of war propaganda, the soldier's experience of war, and the home front's ability to confront the war after the fact. This approach helps literary criticism reject the separation of men's and women's writing, particularly but not only their writing about war.